Head and trunk stabilization strategies during forward and backward walking in healthy adults - Nadeau, Sylvie; Amblard, Bernard; Mesure, Serge; Bourbonnais, Daniel (Gait & posture, 2003)
The purpose of this study was to investigate the head and trunk equilibrium strategies while walking forwards and backwards under different conditions (eyes open vs. closed, hard vs. soft surface) in a sample of 11 consenting healthy adult subjects. Nine markers placed on the subject allowed us to record the kinematics of the head, spine and pelvis segments while walking. The data were acquired and analyzed using an optical TV-image processor (ELITE system). For each locomotor trial, the walking speed as well as the absolute angular dispersions and the anchoring indexes (AI) of six segments around the roll and pitch axes were calculated to assess the head and trunk equilibrium strategies. A three-way repeated measures analysis of variance was used to depict differences between the walking conditions. The results showed that the walking speed was affected by the locomotion tasks ( P<0.05) with values ranging from 1.10±0.21 m s −1 for natural conditions (walking forwards on a hard surface, eyes open) to 0.79±0.15 m s −1 for the most unusual conditions (walking backwards on a foam support, eyes closed). In general, walking backwards reduced the angular dispersion of the spine segments while the absolute angular dispersions of the head and pelvis did not vary significantly with any factors ( P>0.05). The AI around the roll axis indicated good stabilization in space of the head and pelvis with high positive values and this stability increased while the subject was walking backwards on a soft surface (foam). By contrast, the spinal segments were predominantly stabilized on the underlying segment (negative AI), and this stabilization even increased when the subjects walked backwards on a soft surface. Increasing the locomotion difficulty thus induced a generally rigid (‘en bloc’) functioning of the spinal segments and increased effectiveness of the head and pelvis stabilization strategies in space, especially when walking backwards on a soft surface.